A case of polygyny in the Eurasian Wigeon Anas penelope - Jacobsen, Odd W; Ugelvik, Morten (Wildfowl, 1995)
A case of polygyny in the Eurasian Wigeon is described. The presence of a second female (F2) on the male’s defended area in the lake may have been due to an especially high abundance of an important food (chironomids) prior to breeding. During prelaying, egg-laying and parts of the incubation period, the inter-mate distance between the male and the two females decreased. The male became more vigilant as the season progressed when staying with both F1 and F2. It is concluded that guarding by the male must reduce the occurrence of extra-pair copulation attempts on his females in order to increase his own lifetime reproductive success.